Comparative Mediation and Arbitration in Civil Dispute Resolution in Indonesia - Naisabur, Nanang (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The increasing number of civil disputes in Indonesia has created an urgency to find more effective dispute resolution methods to alleviate the burden on the judiciary. This study aims to compare the effectiveness of mediation and arbitration in dispute resolution, as regulated by Supreme Court Regulation No. 1 of 2016 and Law No. 30 of 1999. The normative juridical method was chosen to analyze the relevant legal framework to understand the strengths, weaknesses, and legal impacts of these two methods. This analysis also includes Roscoe Pound’s theory of legal efficiency and Satjipto Rahardjo’s progressive law approach, which emphasizes the importance of legal adaptability. Through this approach, the study is expected to provide comprehensive insights to assist legal practitioners, business actors, and the public in selecting the most appropriate method for efficiently resolving civil disputes. The research finds that mediation and arbitration have distinct advantages in resolving civil disputes in Indonesia; mediation is effective for maintaining relationships and cost-efficiency, while arbitration provides legal certainty with final decisions. Mediation, though fast, relies on formal agreements to be binding, whereas arbitration is more costly and does not permit appeals except under certain circumstances. Understanding these strengths and limitations helps stakeholders choose the most appropriate method to achieve substantive justice and efficiency in practice.